1999
DOI: 10.1002/(sici)1521-4141(199910)29:10<3188::aid-immu3188>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Role of autologous CD4+ T cell clones in human B non-Hodgkin's lymphoma: aborted activation and G1 blockade induced by cell-cell contact

Abstract: This article describes the study of the functional relationship between auto‐tumor‐reactive CD4+ T cell clones (TCC) and autologous malignant B cells. Four auto‐tumor‐reactive CD4+ TCC were derived from tumor‐infiltrating T lymphocytes (TIL‐T) from a freshly isolated human follicular lymphoma by the following technique: total CD4+ TIL‐T were negatively purified by an immunomagnetic procedure, then CD4+ TCC were obtained by limiting dilution in the presence of IL‐2 and autologous non‐irradiated follicular lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…[26][27][28] Therapeutical strategies targeting the interaction of FL cells with their follicular microenvironment might therefore represent attractive approaches to fight tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Therapeutical strategies targeting the interaction of FL cells with their follicular microenvironment might therefore represent attractive approaches to fight tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Table II indicates the results of statistical analysis of the data and precursor frequency. In the real experiment conducted with TIL-T in one case of B cell lymphoma (9), the slope test z derived from the generalized linear log-log model did not reject the SHPM, and it was concluded that the SHPM adequately fits the observed data. In contrast, in the simulated experiment, conducted according to the STTPM, the statistics z clearly rejected the hypothesis that the data conformed to single-hit kinetics.…”
Section: Derivation Of the Stppmmentioning
confidence: 95%
“…According to the Poisson law, the fraction of wells not containing a The first set of data represents a limiting dilution culture aimed at estimating the frequency of IL-2-responsive TIL-T in one case of low-grade, splenic marginal zone lymphoma. The method has been previously described (9). Briefly, total spleen cells were separated into purified TIL-T and purified malignant B cells by using an immunomagnetic procedure.…”
Section: Derivation Of the Stppmmentioning
confidence: 99%
“…The mAb D1.12, recognizing an epitope near the peptide binding groove on the DR␣ chain (29), was used to stimulate the B lymphocytes via HLA-DR (30,31). IL-4 and anti-CD40 mAb, a well-known combination for B lymphocyte activation and proliferation, were applied as well (32,33). Finally, cells were incubated with PMA, a potent B lymphocyte activator via modulation of PKC (34,35).…”
Section: Down-modulation Of Dm and Do Upon In Vitro Activation Of Primentioning
confidence: 99%